Analysis of the Implementation of Management of Village-Owned Enterprises (BUMDES) in Increasing Village Original Income - Bella Dwi Ari Puspita K; Taufiq Hidayat, Muhammad (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
BumDes, short for Village-Owned Enterprises, functions under the Ministry of Village, Development of Disadvantaged Regions, and Transmigration, as outlined in Government Regulation Number 11 of 2021. BumDes, a legally recognized entity formed by a single village or collaboratively by multiple villages, is dedicated to overseeing business operations, maximizing asset utilization, boosting investment and productivity, delivering services, and participating in diverse enterprises. Its fundamental objective is to enhance the well-being of rural communities.This research aims to describe the management of Village-Owned Enterprises (BUMDes) in the Plumpang sub-district, particularly in three villages: Bandungrejo Village, Kepohagung Village, and Kesamben Village. The research method employs qualitative data, with the researcher conducting studies in five villages, including Klotok Village, Bandungrejo Village, and Kepohagung Village. Three informants from each village participated, making a total of nine informants, including the Village Head, BUMDES Administrator, and Village Supervisory Body (BPD).Based on the findings of this research, BUMDes Jaya Makmur contributes 20% each year to the increase in Village Original Income (PADes). Although the amount is relatively small, its contribution has provided significant assistance to the village's economy. Meanwhile, businesses in Klotok Village contribute 45% to PADes, BUMDes Tirto Kencono contributes 60%, and BUMDes Jaya Makmur Sentosa contributes 53%. All BUMDes contribute to PADes and, on average, experience an annual increase.